The Diversity of Lichens in The Tourist Area of The Stokel Waterfall Central Lombok - Suniyanti Suniyanti; Mahrus Mahrus; I Gde Mertha (Jurnal Biologi Tropis, 2022)
Lichen is a symbiosis of fungi and algae cause morphology and physiology are in one unit. It can be an indicator for environmental monitoring, especially as a bioindicator of air pollution, and therefore deserves more attention in the tropics. Data for the diversity and distribution of lichens in the Nusa Tenggara region is still very lacking. Benang Stokel Waterfall Tourism has high potential as a diversity center for exploration that needs attention, including the lichen community. This study aims to know and find the diversity of lichen species in the Benang Stokel Waterfall Tourism Area. Collecting data used two methods, i.e., the exploration method and the transect with 50 plots in size 2m x 2m along the transect line. The lichen diversity index analysis used the Shannon-Wiener Diversity Index, and the species Diversity Index (H') was 2,019 (intermediate category). The study found nine species of lichens: Cryptothecia, Cryptothecia Stirton, Lepraria Lepraria, Lepraria sp., Graphis Scripta, Grapes sp., Opegrapha ara, dan Chiodecton sp., were fully identified.